Intergenerational Income Mobility in New Zealand - Iusitini, Leon Carlton (Auckland University of Technology, 2022)
The transmission of economic advantage and disadvantage within families is a topic of considerable interest to policymakers and the general public in many countries including New Zealand, yet there has been very little research attention directed to understanding the extent to which income persists across generations in New Zealand or the mechanisms by which this occurs. This thesis aims to extend knowledge and understanding of this issue by quantifying and explaining intergenerational income persistence and mobility in New Zealand using two longitudinal data sources. Different analytical approaches are taken to these data sources reflecting differences in the nature of the samples and the income data collected in each. The first data source is the New Zealand Longitudinal Census, a dataset that links census microdata at the individual level over a 32-year timespan. The analysis of this data uses a ‘permanent income’ approach to estimate the intergenerational elasticity of individual total income between son-father, son-mother, daughter-mother, and daughter-father pairs, where sons are born between 1967 and 1979, daughters born between 1967 and 1974, and a proxy for the lifetime average income of offspring and parents is constructed, taking into account well-known sources of measurement error including attenuation and lifecycle biases. The results find that, by international comparison, New Zealand has a relatively low to middling degree of intergenerational income persistence (mobility is average to high), except for persistence between mothers and daughters which is comparatively high. The second data source is the Christchurch Health and Development Study, a longitudinal study tracking a birth cohort of children born in Christchurch, New Zealand in 1977 and followed for 40 years. The analysis of this data adopts a ‘childhood resources’ approach to estimate the intergenerational elasticity and rank correlation of sons’ and daughters’ lifetime average earnings and family income with respect to their parents’ family income over the offspring’s childhood. The results find a high degree of intergenerational income persistence (low mobility) by comparative standards. Both analyses are subjected to a range of robustness checks and sources of bias and limitations are described. Finally, both data sources are used to investigate mechanisms or pathways that mediate the intergenerational association in income, including the role of educational and occupational attainment in adulthood (in both datasets) as well as childhood behavioural problems and cognitive ability (in the Christchurch Health and Development Study). In general, educational attainment and occupation play important roles in intergenerational income persistence, but cognitive skills in childhood also stand out as a key early life mechanism linking parents’ and offspring’s incomes.